Bioactive polymersomes self-assembled from amphiphilic.PPO-glycopolypeptides: synthesis, characterization, and dual-dye encapsulation - Das, Soumen; Sharma, Dharmendar Kumar; Chakrabarty, Suman; Chowdhury, Arindam; Sen Gupta, Sayam (Langmuir, 2015)
Glycopolypeptide-based polymersomes have promising applications as vehicles for targeted drug delivery because they are capable of encapsulating different pharmaceuticals of diverse polarity as well as interacting with specific cell surfaces due to their hollow structural morphology and bioactive surfaces. We have synthesized glycopolypeptide-b-poly(propylene oxide) by ROP of glyco-N-carboxyanhydride (NCA) using the hydrophobic amine-terminated poly(propylene oxide) (PPO) as the initiator. This block copolymer is composed of an FDA-approved PPO hydrophobic block in conjugation with hydrophilic glycopolypeptides which are expected to be biocompatible. We demonstrate the formation of glycopolypeptide-based polymersomes from the self-assembly of glycopolypeptide-b-poly(propylene oxide) in which the presence of an ordered helical glycopolypeptide segment is required for their self-assembly into spherical nanoscale (similar to 50 nm) polymersomes. The polymersomes were characterized in detail using a variety of techniques such as TEM, AFM, cryo-SEM, and light-scattering measurements. As a model for drugs, both hydrophobic (RBOE) and hydrophilic (calcein) dyes have been incorporated within the polymersomes from solution. To substantiate the simultaneous entrapment of the two dyes, spectrally resolved fluorescence microscopy was performed on the glycopeptide polymersomes cast on a glass substrate. We show that it is possible to visualize individual nanoscale polymersomes and effectively probe the dyes colocalization and energy-transfer behaviors therein as well as investigate the variation in dual-dye encapsulation over a large number of single polymersomes. Finally, we show that the galactose moieties present on the surface can specifically recognize lectin RCA(120), which reveals that the polymersomes surface is indeed biologically active.